MU’JIZAT ALQURAN - Ali Anas Nasution (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2018)
This paintingwas titledmiracle ofthe Koran. Conditionof Arabsocietybefore Islamanddowns ofthe Koran, thenthosehabitsarecompiledpoetry, composing poemsorsermons, adviceand counsel. Poemsregarded as beautiful, hungin ka'bahas a tribute to thecomposerat a timeto be enjoyed bytheviewing andreading. Poetgota very specialpositionin Arab society. However, afterthe arrival ofthe Prophetas themessenger of Godtobring thebook ofthe Koran, itturned out to bea habittheyhad no valuewhen comparedwith theKoran.For thatthe Koranhad avery remarkablemiracle.